Pengertian, Landasan, Tujuan dan Kedudukan PAI Dalam Sistem Pendidikan Nasional - Ahmad Husni Hamim; Muhidin Muhidin; Uus Ruswandi (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
This article aims to find out the meaning and meaning, basis, objectives, and position of PAI in the national education system. The research method in this writing uses qualitative methods, namely by means of library research, searching and collecting from various relevant sources. The results of this study indicate that Islamic Religious Education is one of the important subjects in educating the nation's children and forming noble character through religious values ​​that are instilled in children every day. The position of Islamic Religious Education in the National Education system is that religious education is a basic, secondary and higher education that prepares students to be able to carry out roles that require mastery of knowledge about religious teachings or become experts in religious knowledge. Keywords: understanding, foundation, and purpose of PAI, national education